The Environmental Foodprint of Obesity. Issue 1 (20th December 2019) - Magkos, Faidon; Tetens, Inge; Bügel, Susanne Gjedsted; Felby, Claus; Schacht, Simon Rønnow; Hill, James O.; Ravussin, Eric; Astrup, Arne
Abstract : Emissions of greenhouse gases (GHG) are linked to global warming and adverse climate changes. Meeting the needs of the increasing number of people on the planet presents a challenge for reducing total GHG burden. A further challenge may be the size of the average person on the planet and the increasing number of people with excess body weight. We used data on GHG emissions from various sources and estimated that obesity is associated with ~20% greater GHG emissions compared with the normal‐weight state. On a global scale, obesity contributes to an extra GHG emissions of ~49 megatons per year of CO2 equivalent (CO2 eq) from oxidative metabolism due to greater metabolic demands, ~361 megatons per year of CO2 eq from food production processes due to increased food intake, and ~290 megatons per year of CO2 eq from automobile and air transportation due to greater body weight. Therefore, the total impact of obesity may be extra emissions of ~700 megatons per year of CO2 eq, which is about 1.6% of worldwide GHG emissions. Inasmuch as obesity is an important contributor to global GHG burden, strategies to reduce its prevalence should prioritize efforts to reduce GHG emissions. Accordingly, reducing obesity may have considerable benefits for both public health and the environment.